Sleep in Parkinson's disease: A systematic review and meta-analysis of polysomnographic findings. (June 2020) - Zhang, Ye; Ren, Rong; Sanford, Larry D.; Yang, Linghui; Zhou, Junying; Tan, Lu; Li, Taomei; Zhang, Jihui; Wing, Yun-Kwok; Shi, Jie; Lu, Lin; Tang, Xiangdong
Summary: Polysomnographic studies have been conducted to explore sleep changes in Parkinson's disease (PD), but the relationships between sleep disturbances and PD are imperfectly understood. We conducted a systematic review of the literature exploring polysomnographic differences between PD patients and controls in EMBASE, MEDLINE, All EBM databases, CINAHL, and PsycIFNO. 67 studies were identified for systematic review, 63 of which were used for meta-analysis. Meta-analyses revealed significant reductions in total sleep time, sleep efficiency, N2 percentage, slow wave sleep, rapid eye movement sleep (REM) percentage, and increases in wake time after sleep onset, N1 percentage, REM latency, apnea hypopnea index, and periodic limb movement index in PD patients compared with controls. There were no remarkable differences in sleep continuity or sleep architecture between PD patients with and without REM sleep behavior disorder (RBD). Our study suggests that PD patients have poor sleep quality and quantity. Sex, age, disease duration, presence of RBD, medication status, cognitive impairment, and adaptation night are factors that contributed to heterogeneity between studies.